Pelatihan Pemanfaatan Laboratorium Virtual Pada Pembelajaran Fisika Bagi Siswa SMA Negeri 1 Kefamenanu - Fetronela Rambu Bobu; Dian Grace Ludji; Yasinta O.L. Rema (I-Com: Indonesian Community Journal, 2024)
The use of technology in physics education has not been widely implemented, even though the subject is considered one of the more difficult subjects for high school students due to its abstract nature and involvement of many mathematical equations. This issue is also experienced by students from SMA Negeri 1 Kefamenanu. Classroom teaching remains lecture-based and has not yet incorporated technology in physics learning. Students still perceive physics as a difficult and boring subject. Therefore, this Community Service Program (PKM) aims to provide training on the use of technology, specifically utilizing a GeoGebra-based virtual laboratory for the students of SMA Negeri 1 Kefamenanu. The students were trained to use GeoGebra as a virtual laboratory, taking advantage of its features to create simulations and animations on vector and kinematics topics. The results of this training showed that students were very enthusiastic about using GeoGebra as an interactive simulation tool to solve problems related to vector and kinematic concepts. Students also actively participated in creating their own animations on kinematic topics.